Respuesta :
Answer: The solution of the given differential equation is
[tex]y=c e^{\frac{-2}{x} }[/tex]
Step-by-step explanation:
Explanation:-
Step:1
Given differential equation is
x^2 d y /d x = 2 y
By using variable separable that is separating x terms and y terms
[tex]\frac{d y}{2 y} =\frac{d x}{x^2}[/tex]
Step 2:-
Now integrating on both sides we get the solution
[tex]\int\ {\frac{1}{y} } \, d y =\int\limits {\frac{2 d x}{x^2} }[/tex].........(1)
[tex]By using integration formula[/tex]
[tex]\int\limits{\frac{1}{y} } \, d y =logy+c[/tex]......(a)
and By using again integration formula
[tex]\int\limits {x^n} \, d x = \frac{x^n}{n+1}[/tex].....(b)
we will apply these (a)and (b) integration formulas in equation (1)
we get solution is
[tex]logy = 2 \frac{x^{-2+1} }{-2+1} +log c[/tex]
(here you can take integration constant is log c)
Step 3:-
Now simplification
[tex]logy - log c = \frac{-2}{x}[/tex]........(2)
Here you can apply logarithmic formula
[tex]log a-log b=log(\frac{a}{b)}[/tex]
now the equation (2) can be written as
[tex]log(\frac{y}{c}) = \frac{-2}{x}[/tex]......(3)
and again simplify using logarithmic formula
taking logarithmic function base (e) and equating b value
now [tex]a = e^{b}[/tex]........(c)
by using equation (c) formula
now the equation (3) can be written as
[tex]\frac{y}{c} = e^{\frac{-2}{x} }[/tex]
now [tex]y= c e^{\frac{-2}{x} }[/tex]
Final answer :-
[tex]y= c e^{\frac{-2}{x} }[/tex]